A Simple Protocol for Amplification of Genes from Inactivated Oil Adjuvant Fowl Cholera Vaccine - Antony, P.X.; Nair, G.K.; Jayaprakasan, V.; Mini, M.; George, S. (International Journal of Poultry Science, 2006)
Pasteurellosis is one of the most contagious disease of avians. Control of pasteurellosis is at present carried out by vaccination with whole-cell bacterins, which confer serotype specific protection. Outermembrane proteins (OMP) of Gram negative bacteria are considered the most important immunogens and have been proved to confer immunity. A simple protocol for amplification of outermembrane protein genes from inactivated bacterial vaccines has been standardized. An attempt has been made to compare the OMP genes of field isolates and vaccine strain.